2020
DOI: 10.18632/aging.202327
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel immune microenvironment signature predicting survival and therapeutic options for bladder cancer

Abstract: Few studies have investigated the potential of tumor immune microenvironment genes as indicators of urinary bladder cancer. Here, we sought to establish an immune-related gene signature for determining prognosis and treatment options. We developed a ten-gene tumor immune microenvironment signature and evaluated its prognostic capacity on internal and external cohorts. Multivariate Cox regression and nomogram analyses revealed the prognostic risk model as an independent and effective indicator of prognosis. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…The inactivation of suppressor genes encoding proteins regulating DNA repair or apoptosis may also be one possible mechanism (Williams, 2004). Various immune-related pathways are also reported to contribute to the occurrence of bladder cancer (Wu et al, 2020;Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The inactivation of suppressor genes encoding proteins regulating DNA repair or apoptosis may also be one possible mechanism (Williams, 2004). Various immune-related pathways are also reported to contribute to the occurrence of bladder cancer (Wu et al, 2020;Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While most studies were dedicated to explore a single molecule, the functions and mechanisms of these molecules remain far from satisfactory. Presently, many studies have identified models based on expression profiles to improve the potential value of personalized options for BC ( Yan et al, 2020b ; Yan et al, 2021 ). In this study, we depicted the landscape of these 33 pyroptosis genes at the transcriptional and genetic levels and their correlations in BC.…”
Section: Discussionmentioning
confidence: 99%
“…A series of immune-related prognostic gene signatures for bladder cancers have been constructed based on the public datasets obtained from TCGA and GEO databases [36][37][38][39][40][41][42][43]. They usually employed the TCGA-BLCA dataset to build the model and then validated it with a single external GEO dataset.…”
Section: Discussionmentioning
confidence: 99%